2014
DOI: 10.4162/nrp.2014.8.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions of histidine-dipeptides and metabolic syndrome

Abstract: The rapid increase in the prevalence of metabolic syndrome, which is associated with a state of elevated systemic oxidative stress and inflammation, is expected to cause future increases in the prevalence of diabetes and cardiovascular diseases. Oxidation of polyunsaturated fatty acids and sugars produces reactive carbonyl species, which, due to their electrophilic nature, react with the nucleophilic sites of certain amino acids. This leads to formation of protein adducts such as advanced glycoxidation/lipoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 70 publications
(88 reference statements)
2
43
1
1
Order By: Relevance
“…Although the effect of each SNP and dietary factor is small, the combined effect of the genetic and dietary factor is rather strong. CNDP1 and CNDP2 are dipeptidases that are related to the metabolism of carnosine or GSH, respectively [10,11,14,15], which are the most abundant naturally occurring endogenous dipeptide and tripeptide with antioxidant and free radical scavenger properties, respectively [11,12,13,16]. In addition, CNDP2 seems to be a Cys-Gly peptidase of the γ-glutamyl cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effect of each SNP and dietary factor is small, the combined effect of the genetic and dietary factor is rather strong. CNDP1 and CNDP2 are dipeptidases that are related to the metabolism of carnosine or GSH, respectively [10,11,14,15], which are the most abundant naturally occurring endogenous dipeptide and tripeptide with antioxidant and free radical scavenger properties, respectively [11,12,13,16]. In addition, CNDP2 seems to be a Cys-Gly peptidase of the γ-glutamyl cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring endogenous dipeptides containing histidine, such as carnosine, anserine, and homocarnosine, have antioxidant and free radical scavenging properties [10,11,12]. Carnosine is the most abundant dipeptide and plays an important role in humans [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress can activate several inflammation associated transcription factors, including nuclear factor‐kappa B (NF‐κB), activator protein‐1 (AP‐1), P53, signal transducer and activator of transcription 3 (STAT3), hypoxia‐inducible factor‐1α (HIF‐1 α), and NFE2 related factor‐2 (Nrf2), which are involved in the formation of a variety of inflammatory mediators (Lee et al, 2015). Furthermore, oxidation of proteins and lipids generates advanced glycation end products (AGEs), which activate receptor for advanced glycation end products (RAGE) and induce inflammation (Song et al, 2014).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…It has been reported that these molecules can act as efficient scavengers of reactive carbonyl species generated by glucose and lipid oxidation [3][4][5]. In the review reported by Song et al [6], they discuss the reaction mechanism of oxidative stress and certain chronic diseases, the relation between oxidative stress and inflammation, the effective reactive carbonyl species, the glycosylation end products sequestering actions of histidine-dipeptides and their metabolism, the effects of carnosinase encoding gene on the effectiveness of histidine-dipeptides and the protective effects of histidine-dipeptides against progression of metabolic syndrome in http detail. Anserine (L-histidine-b-alanyl-3-methyl) and carnosine (L-histidine-b-alanyl) are two histidine derivatives which are found in skeletal muscles, the heart and the central nervous system at very high concentrations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%